Exploration of cause contributing defect at high-rise residential building in Klang Valley - a literature review / Prem Kumar Paramasivam and Nadzirah Zainordin - Paramasivam, Prem Kumar; Zainordin, Nadzirah (2018)
In Malaysia, construction industry can be known as major productive sector since the construction started in the early 1990s with the development of mammoth projects. Most of the building defects due to human factors were caused solely by forgetfulness and carelessness, lack of knowledge, and a very small percentage were intentional. As for workmanship defects, lack of motivation dominated costs, but the presence of risks directly increased the chance of defects. Hence, it is very important to identify the root of the problems and then must find out the possible solution to solve it. About 20 research papers published within the past 10 years are used in abstracting all the relevant literatures, analysing and coming out with the findings on what are the indicators to be identified and considered as factors of these issue can create an awareness for everyone who are involved in the building's management and maintenance including the building users.